Difficulties in Cataract Surgery 2018
DOI: 10.5772/intechopen.73584
|View full text |Cite
|
Sign up to set email alerts
|

Combined Glaucoma and Cataract: An Overview

Abstract: Glaucoma and cataract frequently coexist in our elderly population regardless of geographical location or ethnicity. Cataract extraction alone has demonstrated to reduce intraocular pressure in eyes either with or without glaucoma. However, this chapter focuses on how cataract surgery might be combined with different glaucoma surgical procedures, such as trabeculectomy, non-penetrating procedures and minimally invasive procedures (MIGS), as well as implantation of drainage devices like the Trabectome ® and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 79 publications
0
4
0
Order By: Relevance
“…Cataract and glaucoma are common diseases with a steeply increasing incidence over the age of 60 years [ 1 ]; both conditions occur more frequently with advancing age. Cataract and glaucoma frequently coexist in our patient population [ 2 ]. They are serious conditions and can cause visual loss.…”
Section: Introductionmentioning
confidence: 99%
“…Cataract and glaucoma are common diseases with a steeply increasing incidence over the age of 60 years [ 1 ]; both conditions occur more frequently with advancing age. Cataract and glaucoma frequently coexist in our patient population [ 2 ]. They are serious conditions and can cause visual loss.…”
Section: Introductionmentioning
confidence: 99%
“…Cataract surgery alone is considered to result in long-term IOP reduction. The mechanism behind IOP reduction through cataract surgery is still controversial [ 13 , 14 , 15 ]. Compression of Schlemm’s canal is assumed to follow an increase in lens volume with age, providing traction over the zonules and subsequently on the ciliary body.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a short-term increase in pressure during cataract surgery may lead to increased patency in the trabecular meshwork and Schlemm’s canal. Despite the existence of all these theories, disagreement still exists on the potency, clinical importance, and long-term variability of each process [ 13 , 14 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cataracts and glaucoma are the top two leading causes of blindness in individuals above 50 years, with a global prevalence of 15.2 and 3.6 million cases, respectively, in 2020 [1]. As the prevalence of these two diseases increases with age, it is not uncommon to find them coexisting together in a single individual [2][3][4][5]. Some studies have even suggested that glaucoma is a risk factor for cataract development and progression [6][7][8].…”
Section: Introductionmentioning
confidence: 99%